Effects of a Structured Media Literacy Intervention on Digital Misinformation Susceptibility Among Undergraduate Students: A Quasi-Experimental Study - Edison Bonar Tua Hutapea; Asep Soegiarto; Totok Ony Wijanarko (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Digital misinformation poses a significant and growing challenge to university students. They are among the most active consumers of online information, yet frequently struggle to distinguish credible content from fabrications. Despite widespread digital fluency, approximately 38% of students incorrectly evaluate the veracity of news headlines under controlled conditions. This study examined the prevalence of misinformation susceptibility among university students and evaluated the effectiveness of a structured, inoculation-grounded media literacy intervention. Using a quasi-experimental mixed-methods design, 200 undergraduate students were assigned through quota sampling to an intervention group (n = 100) and a waitlist control group (n = 100). No random assignment was employed; groups were matched on key demographic variables. Instruments included the Critical Media Literacy Self-Perception Instrument (CMLSPI; Neira et al., 2024) and the Misinformation Susceptibility Test (MIST-16; Maertens et al., 2024), both adapted into Bahasa Indonesia via forward-backward translation. Cronbach's alpha was .86 (CMLSPI) and .79 (MIST-16). Quantitative results demonstrated statistically significant gains in fake news detection accuracy (30% improvement; Cohen's d = 1.44, 95% CI [1.18, 1.70], p < .001) and self-perceived media literacy (eta2 = .18, p < .001) relative to the control group. Qualitative thematic analysis identified four themes: increased metacognitive awareness, adoption of verification strategies, recognition of cognitive and emotional manipulation, and structural barriers to sustained practice. These findings support the integration of inoculation-based prebunking with MIL competency training as an effective and theoretically grounded approach to building digital resilience among undergraduate students in Indonesia.